The use of computer assisted semen analysis to predict fertility in Holstein bulls - Pepper-Yowell, Amanda Rae, author; Enns, Mark, advisor; Crews, Denny, committee member; Blackburn, Harvey, committee member; Graham, James, committee member (Colorado State University. Libraries, 2011)
Cryo-preserved semen from 120 Holstein bulls was obtained from three semen companies, which were randomly coded 1:3 to decrease bias, through USDA-ARS, Fort Collins, CO. Computer assisted semen analysis (CASA; HTM-IVOS, Version 10.8, Hamilton Thorne Research, Beverly, MA, USA) was used to assess seminal characteristics and to determine if this was useful for predicting fertility, defined in this study as sire conception rate (SCR). For this study the primary CASA measurements assessed were percent motility, percent progressive, average pathway velocity (VAP), straightline velocity (VSL), curvilinear velocity (VCL), amplitude of lateral head displacement (ALH), beat cross frequency (BCF), straightness (STR), linearity (LIN) and cell size (SIZE). Percent motile and percent progressive sperm cells had means, followed by their standard deviation, of 60.93 ± 10.09 and 32.46 ± 10.06%, respectively with percent motile having the lowest coefficient of variation of 16.72 %. Amplitude of lateral head displacement and BCF were both high when compared to other studies conducted with fresh and cryopreserved semen (Budworth et al., 1988, Farrell et al., 1998) with means, followed by their standard deviation, of 8.45 ± 3.5µm and 30.99 ± 9.27Hz, respectively. Straightness and LIN had means, followed by their standard deviation of 80.74 ± 17.11 and 48.24 ± 16.15%, respectively; SIZE had a mean, followed by its standard deviation, of 8.38 ± 2.88µm2. After initial data exploration the data was fit either untransformed, or transformed. Data was fit untransformed because of the data being normally distributed or because a cubic model fit best. Data was fit transformed to better fit normality requirements, for prediction of CASA values. SIZE appeared to have a cubic relationship with all three velocity parameters (VAP, VCL and VSL). The number of bull samples originating from each semen company is as follows: Semen Company 1(SC1) - 32, Semen Company 2(SC2) -71, and Semen Company 3 (SC3) -17. Semen company, when fit as a fixed effect was found to be significant (P ≤ 0.05) so this study looked at the differences of the least squares means between semen companies. When looking at untransformed data SC1 and SC2 were significantly (P ≤ 0.001) different across VAP, ALH and BCF. The heritability of most seminal parameters was low, with the exception of percent motile (0.793). Percent motile also had the greatest genetic variance when compared to its residual variance. Genetic correlation of VAP, ALH and SIZE with SCR were low (0.05, 0.006, and 0.04 respectively); however, percent motile was moderately genetically correlated with SCR at 0.302. After VAP and ALH were transformed to meet normality requirements, heritability was once again calculated and the heritability of the transformed data was lower than the untransformed data. The genetic correlations between the transformed data and SCR stayed the same (0.052) or improved (0.02) (log10VAP and √ALH, respectively). The low heritabilities of these seminal traits does not make them good candidates for genetic evaluation. Significant differences between semen companies suggest that the methods semen companies use to select bulls, collect semen from bulls, extend semen and store the cryopreserved semen could be different. However, this information is highly proprietary and is difficult to ascertain to truly attribute difference between semen companies. Due to the genetic correlations between CASA values and SCR being low we were unable to use this study's CASA values for genetic prediction of fertility. While CASA values do have an underlying genetic component, environmental effects are too large and physiological processes vary too much to estimate future performance of these bulls' fertility.
Keywords: CASA; Holstein bulls; fertility